Conifer By-Products Extracted Using Hydrodynamic Cavitation as a Convenient Source of Phenolic Compounds and Free Amino Acids with Antioxidant and Antimicrobial Properties - Luisa Pozzo; Andrea Raffaelli; Lidia Ciccone; Federica Zabini; Andrea Vornoli; Vincenzo Calderone; Lara Testai; Francesco Meneguzzo (Molecules)
Softwood bark and twigs represent by-products of forest supply chains rich in extractable bioactive compounds. This study aimed at evaluating the bioactive molecules of hydrodynamic cavitation (HC) based extracts of bark and twigs from different conifer plants and exploring their antioxidant capacity. Samples of Picea abies twigs (RAR) and bark (CAR) and Abies alba twigs (SFT) underwent extraction using a pilot-scale Venturi reactor HC device. The freeze-dried extracts were characterized for the antioxidant capacity, through both in vitro and ex vivo assays, the antimicrobial activity, and the content of phenolics and free amino acids by UHPLC-ESI-MS/MS. HC-based aqueous extracts were obtained quickly and with low energy consumption. We found 10 phenolic acids, nine flavonols, three flavan-3-ols, five flavanones, three procyanidins, two stilbenoids, and 10 other phenolic compounds. Moreover, eight essential and seven dispensable amino acids were found. The principal component analysis showed clear discrimination among the three extracts. The CAR extract showed antimicrobial activity. The SFT extract showed the higher anthocyanins content and antioxidant activity, both through in vitro and ex vivo methods. These preliminary results confirm that by-products of Picea abies and Abies alba are rich in bioactive compounds and antioxidant activities, suggesting potential applications in the nutraceutical and pharmaceutical fields.